HAYMAN COMPRESSION SUTURES : AN UNDERUTILIZED TOOL FOR MANAGEMENT OF UTERINE ATONY AND POSTPARTUM HAEMORRHAGE. (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Postpartum hemorrhage (PPH) is the leading cause of maternal mortality in low- andmiddle-income countries. Uterine atony accounts for 70–80% of PPH cases. Management of PPH isusually based on a cascade beginning with the use of uterotonics and eventually hysterectomy in casesof refractory PPH. Different compression suture techniques have been described and used for themanagement of uterine atony where medical management is insufficient and preservation of fertility isdesired.Case presentation: This is a series of four patients who presented to our facility and consequentlydeveloped uterine atony that was unresponsive to medical management during cesarean delivery despitethe use of multiple uterotonics. All four patients had established risk factors for uterine atony, includinginduction of labor, augmentation of labor, chorioamnionitis, or fetal macrosomia. Hayman compressionsutures were performed in all four patients with success. Estimated blood loss in the series ranged from400 to 1200 mls. All patients recovered well with no complications reported during the postpartum period.Conclusion: Hayman compression sutures offer an alternative to the more ubiquitous B-Lynch suturewith several advantages, including ease of placement and no need for a hysterotomy in PPH post vaginalbirth or placement post repair of hysterotomy in cesarean cases. Thus, the may be easier to perform forjunior health care professionals as well as in stressful situations.